Officium et ius in the can. 1136 Code of Canon Law - BARTCZAK, ADAM (Prawo Kanoniczne, 2014)
The concept of the duty and the right functions in the Code of Canon Law. We can found it in the can. 1136. The Legislator defines this concept very characteristic. In this canon following some phrase: gravissimum officium et ius primarium. Such a definition in the Code is only at this point. It is true that the Legislator is not consistent in the use of this terminology. The analysis of that term indicates that the form of expression has its source in the concept of family. The family is the first place where the person develops. Those who gave life have the heaviest duty and the very first right to educate their offspring. Parents can not get rid of it because it is naturally inscribed to be a mother and a father.